2003
DOI: 10.1891/vivi.2003.18.3.259
|View full text |Cite
|
Sign up to set email alerts
|

Men Who Use Violence: Intimate Violence Versus Non-Intimate Violence Profiles

Abstract: The current study examined the differences between three types of violent men based on Holtzworth-Munroe and Stuart's (1994) tripartite typology and a group of non-intimate violent men. First, a cluster analysis was conducted on a sample of 91 domestically violent men, resulting in three clusters that approximated the tripartite model for psychopathology as measured by the MMPI-2, that is, non-pathological, borderline/dysphoric, and antisocial. Based on the violence variables (i.e., severity of violence, famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 46 publications
6
36
1
Order By: Relevance
“…First, continued evidence supporting the existence of male, intimate partner violence batterer subtypes was revealed. This study exposed four subtypes of male IPV batterers, similar in characteristics to the four subtypes revealed by Holtzworth‐Munroe and associates (), and affirmed by others (Hamberger et al., ; Huss & Ralston, ; Langhinrichsen‐Rohling et al., ; Lawson et al., ; Thijssen & de Ruiter, ; Tweed & Dutton, ; Waltz et al., ). The present study demonstrated that these classifications could be accurately obtained, even with crude measures.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…First, continued evidence supporting the existence of male, intimate partner violence batterer subtypes was revealed. This study exposed four subtypes of male IPV batterers, similar in characteristics to the four subtypes revealed by Holtzworth‐Munroe and associates (), and affirmed by others (Hamberger et al., ; Huss & Ralston, ; Langhinrichsen‐Rohling et al., ; Lawson et al., ; Thijssen & de Ruiter, ; Tweed & Dutton, ; Waltz et al., ). The present study demonstrated that these classifications could be accurately obtained, even with crude measures.…”
Section: Discussionsupporting
confidence: 83%
“…Waltz, Babcock, Jacobson, and Gottman () analyzed a sample of men using intimate partner reports of violence and clinical scales. Lawson and associates () studied a sample of convicted domestic batterers serving sentences on probation. All four of these studies produced three‐cluster solutions with batterer subtypes very similar in characteristics to those identified by Holtzworth‐Munroe and Stuart ().…”
Section: Literature Reviewmentioning
confidence: 99%
“…Findings have been generally supportive, with some research finding evidence of these three groups (Langhinrichsen-Rohling et al, 2000;Lawson et al, 2003). For example, using data gleaned from several sources (e.g., wife reports, number of assaults by the man outside the family, and personality scales from the Millon Clinical Multiaxial Inventory), Waltz, Babcock, Jacobson, and Gottman (2000) found three subgroups.…”
Section: Introductionmentioning
confidence: 88%
“…Research on the extent to which those who commit IPV are generally violent men with an underlying hostility, those with personality pathology, or 'family only' perpetrators has been a question widely investigated in clinical and community samples (Holtzworth-Munroe et al, 2000;Lawson et al, 2003;Tweed & Dutton, 1998;Weinstein et al, 2012). Findings have been generally supportive, with some research finding evidence of these three groups (Langhinrichsen-Rohling et al, 2000;Lawson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Holtzworth-Munroe and Stuart (1994) (Hamberger et al, 1996;Langhinrichsen-Rohling et al, 2000a;Lawson et al, 2003;Tweed & Dutton, 1998;Waltz, Babcock, Jacobson, & Gottman, 2000;Wray, Hoyt, Gerstle, & Leitman, 2015). Extending the typology, the authors (HoltzworthMunroe, Meehan, Herron, Rehman, & Stuart, 2000) added another subtype known as low level anti-social perpetrators which has also been supported through research (Huss & Ralston, 2008;Loinaz, 2014;Thijssen & de Ruiter, 2011).…”
Section: Holtzwoth-munroe's Typologymentioning
confidence: 97%